Biocontrol Rhizobacterium Pseudomonas sp. 23S Induces Systemic Resistance in Tomato (Solanum lycopersicum L.) Against Bacterial Canker Clavibacter michiganensis subsp. michiganensis - Takishita, Yoko; Charron, Jean-Benoit; Smith, Donald L. (Frontiers in Microbiology, 2018)
Tomato bacterial canker disease, caused by Clavibacter michiganensis subsp. michiganensis (Cmm) is a destructive disease and has been a serious concern for tomato industries worldwide. Previously, a rhizosphere isolated strain of Pseudomonas sp. 23S showed antagonistic activity towards Cmm in vitro. This Pseudomonas sp. 23S was characterized to explore the potential of this bacterium for its use in agriculture. Pseudomonas sp. 23S possesses ability to solubilize inorganic phosphorus, and to produce siderophores, indole acetic acid, and hydrogen cyanide. The strain also showed antagonistic activity against Pseudomonas syringae pv. tomato DC 3000. A plant assay indicated that Pseudomonas sp. 23S could promote growth of tomato seedlings. The potential of treating tomato plants with Pseudomonas sp. 23S to reduce the severity of tomato bacterial canker by inducing systemic resistance (ISR) was investigated using well characterized marker genes such as PR1a [salicylic acid (SA)], PI2 [jasmonic acid (JA)], and ACO [ethylene (ET)]. Two-week-old tomato plants were treated with Pseudomonas sp. 23S by soil drench, and Cmm was inoculated into the stem by needle injection on 3, 5, or 7 days post drench. The results indicated that plants treated with Pseudomonas sp. 23S, 5 days prior to Cmm inoculation significantly delayed the progression of the disease. These plants, after 3 weeks from the date of Cmm inoculation, had significantly higher dry shoot and root weight, higher levels of carbon, nitrogen, phosphorus, and potassium in the leaf tissue, and the number of Cmm population in the stem was significantly lower for the plants treated with Pseudomonas sp. 23S. From the real-time quantitative PCR (qRT-PCR) analysis, the treatment with Pseudomonas sp. 23S alone was found to trigger a significant increase in the level of PR1a transcripts in tomato plants. When the plants were treated with Pseudomonas sp. 23S and inoculated with Cmm, the level of PR1a and ACO transcripts were increased, and this response was faster and greater as compared to plants inoculated with Cmm but not treated with Pseudomonas sp. 23S. Overall, the results suggested the involvement of SA signaling pathways for ISR induced by Pseudomonas sp. 23S.